Summer of secrets ebook - Hubbard, Charlotte (Seasons of the Heart., 2011)
First in an Amish romance series from the author of the Promise Lodge novels, "a heartwarming new voice for fans of Beverly Lewis" (Emma Miller, author of An Amish Mystery series). Welcome to Willow Ridge, Missouri! In this cozy Amish town along the banks of the river, the Old Ways are celebrated at the Sweet Seasons Bakery Café, and love is a gift God gives with grace . . . Summer has come to Willow Ridge, but Rachel Lantz is looking forward to a whole new season in her life—marriage to strapping carpenter Micah Brenneman, her childhood sweetheart. When a strange Englischer arrives in the café claiming to be the long-lost sister of Rachel and her twin Rhoda, Rachel feels the sturdy foundation of her future crumbling—including Micah's steadfast love. As the days heat up and tempers flare, Rachel and Micah will learn that even when God's plan isn't clear, it will always lead them back to each other . . . "Hubbard centers her new inspirational series on the Sweet Seasons Café, where everyone in Willow Ridge, Mo., knows your name . . . those who enjoy a glimpse of the culture will find the story appealing."— Publishers Weekly "Hubbard begins a new Amish series, Seasons of the Heart, with lovable characters who are learning that God has more in store for them than they realize. Hubbard will amaze readers with her knowledge of Amish living."— RT Book Reviews Seasons of the Heart series praise "Fans of Amish fiction will love the Seasons of the Heart series."—Marta Perry, national bestselling author "These very special books will sit proudly on my keeper shelf!"— Romance Reviews Today